Petroleum Geoscience - Bjørlykke, Knut (Springer, 2015)
The second edition of Petroleum Geoscience is an updated and corrected version of the first edition from 2010 and there are also four new chapters. Petroleum geology and geophysics are not well-defined academic subjects. They include many different aspects of the Earth sciences which are used in petroleum exploration and production. Nearly all types of insight can in some cases be useful in petroleum exploration and production, but there are some disciplines that are most relevant. Since petroleum is formed and for the most part hosted in sedimentary rocks, sedimentology is critical. Palaeontology is important for dating rocks, and carbonate reservoirs may consist mostly of fossils. Structural geology and basin analysis are also vital for reconstructing the migration and trapping of petroleum. Geochemistry and petroleum chemistry are also important. About 50% of the geoscientists in the petroleum industry are involved with production rather than exploration and we have added a chapter on reservoir modelling written by experts from Statoil Norway. Geophysical methods are essential for logging and seismic exploration, and recently electromagnetic methods have also been more commonly used in exploration and production. This is covered in a new chapter. We have also added a chapter on CCS (Carbon Capture and Storage). The chapter on well logging has been rewritten and is now more comprehensive. Most universities do not offer specific courses in petroleum geology/geophysics and only a few have Masters or PhD programmes in this field. Oil companies therefore recruit many geologists with little training in these subjects. In this book, we have tried to give a basic introduction to disciplines relevant to petroleum exploration and we have also included some aspects of petroleum production and modelling. Since so many different disciplines are included in this book, it is clear that it has not been possible to make in-depth treatments of all of these. This book provides a relatively condensed and precise presentation of the basic theories and facts in each subject and it was therefore necessary to limit the number of field examples and cases
From Sedimentary Environments to Rock Physics